Violence surpassing innocence in Lord of the Flies by William Golding and The Bloody Chamber by Angela Carter - Ayşe Demir (Literacy Trek, 2019)
Of all the instinctive feelings shared by every living being all around the world, there is a collective drive in nature called violence. From the most primitive tribes to the post-modern era of present day, violence is the most basic feeling lying under everyone's psychology. Sigmund Freud claims that the human psychology is divided into three basic parts; namely, id, ego and superego. Id is the part in which all the instinctual feelings including violence is sheltered and Freud suggests that it is one of the basic human instincts in shaping the human life. No matter what a person's age, statue, gender or culture is, from the four-year-old baby to the serial killer, sometimes an angry neighbor and sometimes a looter; the same instinctual desire to harm and the feeling of violence exist in human nature. In other words, violence is explicit in every handle of the live. It would certainly be impossible not to see the reflections of such a shared feeling in literature. Throughout ages, many literary works have focused on this intinction either as the social violence on individuals, or physical violence of characters on the other people, or psychological violence the characters are exposed to. As the writers of post-1950 period, Angela Carter and William Golding display the violence of the characters in a different way in their works Lord of the Flies and The Bloody Chamber. The aim of this study is to analyze how the feeling of innocence is surpassed by the violence through deconstructing the basics of life together with detailed references to these works.